The American declaration of independence of 1776 and the constitution of 1789: A case of their indirect impact on the Greek constitutional order during the war of independence - Trombetas, Thomas P. (The Greek Review of Social Research, 1975)
[Δε διατίθεται περίληψη / no abstract available]